Hubungan antara Indeks Massa Tubuh pada Awal Kehamilan dan Kenaikan Berat Badan Ibu dengan Perdarahan Pasca Salin - Maqfiro, Siska Nawang Ayunda; Mutalib, Rasmin Hi. Abd (Poltekkes Kemenkes Maluku, 2023)
The number of maternal deaths in Indonesia caused by postpartum bleeding can occur vaginally or sectio caesarean. This can be reduced if every mother is able to access quality health services from pregnancy to postpartum and health workers immediately make referrals if complications occur. The aim of this study was to determine the relationship between body mass index in early pregnancy and postpartum bleeding and the relationship between maternal weight gain and postpartum bleeding. This research uses design cross sectional. The population is 465 patients in the delivery room at the Tidore Islands City Hospital in August 2020-August 2021, using a total sampling technique, using secondary data from census books in the delivery room and medical records room at the Tidore Islands City Hospital and recorded in a collection sheet. data. Test results chi-square between the body mass index variable and postpartum hemorrhage, the p value = 0.000, there is a significant relationship with the contingency coefficient value (0.534). Test results chi-square between the variable maternal weight gain and postpartum bleeding, the p value = 0.000, there is a significant relationship with the contingency coefficient value (0.344). So it is very important to monitor weight gain during pregnancy as a form of early detection of postpartum bleeding.